“Relações dos compostos de carbono com a ecologia funcional de comunidades de restinga” - Zorzanelli, Maria Cecília (2023)
The vegetation of the Paulo César Vinha State Park-PEPCV (20°35'25'' S and 40°25'24'' W), Guarapari-ES, is recognized as a model for studying the effects of environmental gradients and possible impacts of climate change on their communities. Some of the variables that we can use in this type of study are the cell wall polymers-CWP (cellulose, hemicelluloses and lignin) and the nonstructural carbohydrates-NSC (sucrose, glucose, fructose and starch) because they have a fine connection with the ecological theories of niche partitioning and distribution of forest species. We hypothesized that the PPC and CNE contents present close correlations with the edaphic gradients of soil moisture and fertility. To test this hypothesis, we collected samples of canopy branches of 35 species distributed in 42 plots (25 m2 /each) of the floodable, intermediate and dry forests of the PPCV restinga. We measured the depth of the water table and collected samples to determine the physical and chemical parameters of the soil along the plots. The CWP and NSC were correlated with the sampled variables, and showed that the cellulose, hemicellulose and fructose contents increased as the species were replaced towards a drier and more porous environment. Boron (B) was the nutrient that most contributed to cellulose deposition, while calcium (Ca2+) was the one that most correlated with hemicelluloses and lignin. These results suggest the participation of B in the synthesis of cellulose fibers and Ca2+ in the synthesis of lignin. The greater deposition of cellulose and hemicellulose of the restinga dry forest species can be interpreted as a way for plants to maintain cellular turgor pressure, allowing growth under less water availability. Lignin did not vary along soil moisture gradients. However, it increased with the availability of Ca2+ in the soil, suggesting the participation of this element in the wood lignification. Regarding CNE, the increase of fructose in drier environments indicates the osmoregulatory role of this molecule under water restriction conditions, while the increase of glucose in the flooded restinga environment seems to be strongly influenced by Al3+ associated with a more acidic pH. On the other hand, starch and sucrose did not show important correlations with the gradients of humidity and fertility, suggesting that for restinga species it is more interesting to convert sucrose into glucose and fructose, which seem to act in osmotic control in environments with greater toxicity of Al3+ and low water availability. Thus, soil moisture and fertility gradients are selecting traits with ecological functions within plant communities as a way of adapting to environmental conditions. We conclude that PPC and CNE act as important functional trait in restinga communities, reinforcing the importance of structural and non-structural carbon to study the impacts of climate change on plant communities.